Behavioral Ratings of Executive Functioning Explain Instrumental Activities of Daily Living beyond Test Scores in Parkinson's Disease. Issue 1 (2nd January 2016) - Puente, Antonio Nicolas; Cohen, Matthew L.; Aita, Stephen; Brandt, Jason
Abstract : Objective : Executive dysfunction is common in Parkinson's disease (PD), yet the relationship between executive functioning (EF) and instrumental activities of daily living (IADLs) is inconsistent. This inconsistency may be due to the limited relationship between EF test scores and behaviors. Rating scales provide a potential way to supplement test scores in predicting patient's ability to complete IADLs by capturing a wide range of EF behaviors in their everyday environment. We hypothesized that informant-rated EF would provide incremental validity in predicting IADLs above and beyond EF test scores. Methods : Eighty-five patients were selected from a clinical neuropsychological database of PD patients evaluated for deep brain stimulation surgery at The Johns Hopkins Hospital between September 2006 and January 2015. Hierarchical regression was completed to determine the relationship between an EF behavioral rating scale (i.e., FrSBe), EF test scores, and IADLs. Results : The EF behavioral rating scale added incremental validity to neuropsychological test scores in predicting IADLs. Conclusions : Behavioral ratings of EF may provide additional information about how PD patients' EF is influencing their everyday life.